The Nodal Non-Hodgkin’s Lymphoma: Histomorphological Study with Special Emphasis on Immunomarker Profile of Nodal NHL - Patel, Jaimini Nisarg; Gupta, Shubha Rakesh; Faujdar, Mansi; Patel, Nisarg Prakash (Annals of Pathology and Laboratory Medicine, 2019)
Background: Lymphoid malignancies (LM) are a heterogeneous group of disorders that are broadly divided into Hodgkin disease (HD) and Non-Hodgkin Lymphoma (NHL). Diagnosing lymphoid malignancies based on morphology in conjunction with immunohistochemistry (IHC) forms the basis of WHO classification and this has prognostic implications. The distribution of the major subtypes of non-Hodgkin’s lymphoma (NHL) differs across geographic regions. Material & Method: Over all 147 cases of NHL over a period of 16 months (between March 2014 and June 2015) were diagnosed in the Department of Histopathology, Santokba Durlabhji Memorial Hospital cum Medical Research Institute, Jaipur. Of the total of cases of lympho-proliferative disorders, the diagnosis of NHL was done by light microscopy alone and was classified according to International Working Formulation initially. All the cases diagnosed provisionally as NHL were taken up for immunophenotyping with Immunohistochemical (IHC) studies. The individual NHL cases were classified according to the WHO/REAL classification according to the positive or relevant negative immonophenotypic expression and tabulated to ascertain the morphological spectrum of NHL in this part of the country. Out of 147 cases of provisionally diagnosed NHL, 144 cases confirmed as NHL by IHC study. Overall concordance between light microscopy and IHC was 97.96%. Results: B-cell lymphomas formed 88.89%, T-cell lymphomas formed 8.33% and unclassified NHL formed 2.78% of nodal NHLs. Diffuse Large B-Cell Lymphoma (DLBCL) was the most common subtype (61.11% of all NHLs). B-cell small lymphocytic lymphoma, Follicular lymphomas, Mantle-Cell Lymphoma (MCL), marginal zone B-cell lymphomas, Burkitt’s lymphoma and B cell lymphoblastic lymphoma amounted to 11.11%, 5.56%, 4.16%, 2.78%, 1.39% and 1.39% respectively. Among the T-cell lymphomas, T-cell lymphoblastic lymphoma, anaplastic large-cell lymphomas of T/null-cell type, and Angioimmunoblastic T-cell lymphoma (AITL) accounted for 4.16%, 2.78%, and 1.39% of all NHL cases, respectively.